Rationale for Shallow Foundation Rocking Provisions in ASCE 41-13. Issue 2 (May 2016) - Kutter, Bruce L.; Moore, Mark; Hakhamaneshi, Manouchehr; Champion, Casey
ASCE 41-13 supports three methods of modeling the soil-structure interaction for rocking footings as components of a foundation-building system: Method 1 uses uncoupled moment, shear, and axial springs; Method 2 uses a nonlinear gapping bed of springs; and Method 3 is used for structural footings that are flexible relative to the underlying soil. New component action tables in ASCE 41-13 provide modeling parameters and acceptance criteria for nonlinear and linear analysis of shallow foundation components. The values in the component action tables for nonlinear procedures were largely based upon analysis of foundation performance in model tests on rocking foundations. The primary measure to assess foundation performance is residual settlement or uplift. The acceptance criteria for linear analysis procedures ( m -factors) were derived from the allowable rotations for nonlinear procedures. A design example is presented in an onlineAppendix to illustrate differences between the current and previous versions of ASCE 41 and ASCE 31.